Key role of quinone in the mechanism of respiratory complex I - Javier Gutiérrez-Fernández (Nature Portfolio, 2020)
Complex I (NADH:ubiquinone oxidoreductase) is the first enzyme of the respiratory chain in bacteria and mitochondria. Here, the authors present cryo-EM and crystal structures of T. thermophilus complex I in different conformational states and further analyse them by Normal Mode Analysis and molecular dynamics simulations and conclude that quinone redox reactions are important for the coupling mechanism of complex I.